Duch Święty jako żywioły natury w symbolicznych interpretacjach Starego Testamentu w tradycji łacińskiej - Bardski, Krzysztof (Verbum Vitae, 2020)
The article is the fruit of research on the patristic and medieval symbolism of the Holy Spirit, based on the texts of the Old Testament, as expressed through the help of images of elements of nature, such as wind, water and fire. The most important of such interpretations belonging to the traditions of the Latin Church are presented and discussed.